Fault diagnose based on pattern recognition - Liu, Zhuoshi. (2013)
This is a joint project with SIMTech. It is mainly focusing on developing a fault diagnose system. The system can be used to solve stochastic and dynamical problems, like bank abnormal transaction detection, operation abnormal event detection and equipment failure event detection.